Synthesis and spectroscopic analysis of Eu3+-doped tungsten bronze Sr5YTi3Nb7O30 phosphors for w-LED and visualization of latent fingerprint. Issue 3 (1st February 2022) - Ma, Yingying; Liu, Ruiyuan; Geng, Xue; Hu, Xiaopeng; Chen, Wensheng; Deng, Bin; Yu, Ruijin; Geng, Huiling
Abstract: A series of novel Sr5YTi3Nb7O30: x Eu 3+ ( x  = 0.05–0.40) red-emitting phosphors were firstly synthesized using the high-temperature solid-state method. The X-ray diffraction (XRD) patterns demonstrate that the phosphors are pure phase with the space group P 4 bm of tetragonal system. Under the 395 nm excitation wavelength, the red emission of Sr5YTi3Nb7O30:Eu 3+ phosphor is considered to be dominated by the 5 D0 → 7 F2 transition at 613 nm. The asymmetry ratios (R/O) of Sr5YTi3Nb7O30: x Eu 3+ ( x  = 0.05–0.40) phosphors are identified as 2.64–2.78, which contribute to the high color purity (99.5%–99.8%). The phosphor has good thermal stability with 0.17 eV of activation energy. The Commission International de L'Eclairage (CIE) coordinates of the w-LED nearly overlap with the standard white light (0.333, 0.333), the Ra is as high as 90. Meanwhile, the features of fingerprint are simultaneously distinguished at three levels on aluminum foil by Sr5YTi3Nb7O30:0.30Eu 3+ phosphor. In addition, the latent fingerprint on various nonporous substrates (stainless steel, glass, and plastic surfaces) were identified. In summary, the phosphor is feasible to apply in the w-LEDs and latent fingerprint detection.